Health Counseling: Efforts to Maintain Elderly Health Through Healthy and Happy Tips in Old Age in Geulanggang Village, Gampong - SITEPU, EKA LESTARI; Siregar, Anggi Pramono (Jurnal Pengabdian West Science, 2025)
Living a healthy and happy life in old age is the dream of many people. Therefore, it is necessary to pay attention to health from various aspects of life, through a health education approach. The health counseling program carried out in the Village of Kab Bireun aims to increase the elderly's understanding of health and can remain happy in old age. This activity targets all elderly in Geulanggang Gampong Village, Kab. Bireuen and collaborates with Lazimu Bireuen and the Setia memberi Sesama foundation as providers of facilities and infrastructure. This activity took place on March 19, 2025 in Geulanggang Gampong Village, Kab. Bireuen. The method of this activity is a structured health counseling activity, namely checking the elderly's blood pressure, measuring their weight, and followed by an interactive discussion session. The evaluation results showed a significant increase in understanding of healthy and happy tips in understanding stress management and a strong encouragement to do physical activity and improve diet. So this activity indicates the success of the program in achieving the desired goals.
Keywords: Elderly, Health Education, Health Tips